NILAI-NILAI PENDIDIKAN AKHLAK DALAM UMPASA MASYARAKAT ADAT SIMALUNGUN - Saiful Akhyar Lubis, Amiruddin Siahaan, Alkausar Saragih (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The purpose of this study was to determine the pattern of umpasa-based moral education in the family of the Simalungun Muslim indigenous community. This study used qualitative research methods, namely, through observation, observation, interviews, or document review. The sample consisted of 3 districts, namely Raya District, Siantar District, Bandar Huluan District, each district consisting of 5 villages and one village consisting of 5 samples. The moral content in the Simalungun example is: Umpasa is worth honesty, Umpasa is worth modesty, Umpasa is worth keeping promises, Umpasa is worth hard work, Umpasa is worth peace, Umpasa is worth loving, Umpasa is worth forgiving, Umpasa is worth trusting, Umpasa is worth thanks, Umpasa worth helping, Umpasa is worth prayer / hope, Umpasa is worth not giving up easily, Umpasa is worth building a harmonious relationship, Umpasa is worth not hearing advice.